Clinical Immunoassay for Human Hepcidin Predicts Iron Deficiency in First-Time Blood Donors. (24th April 2020) - Gutschow, Patrick; Han, Huiling; Olbina, Gordana; Westerman, Keith; Nemeth, Elizabeta; Ganz, Tomas; Copeland, Karen; Westerman, Mark; Ostland, Vaughn
Abstract: Background: Serum markers currently used as indicators of iron status have clinical limitations. Hepcidin, a key regulator of iron homeostasis, is reduced in iron deficiency (ID) and increased in iron overload. We describe the first CLIA-validated immunoassay with excellent accuracy and precision to quantify human serum hepcidin. Its diagnostic utility for detecting ID in first-time blood donors was demonstrated. Methods: A monoclonal competitive ELISA (C-ELISA) was developed for the quantitation of human hepcidin and validated according to CLIA guidelines. Sera from nonanemic first-time blood donors (n = 292) were analyzed for hepcidin, ferritin, transferrin, and serum iron. Logistic regression served to determine the utility of hepcidin as a predictor of ID. Results: The C-ELISA was specific for human hepcidin and had a low limit of quantitation (4.0 ng/mL). The hepcidin concentration measured with the monoclonal C-ELISA was strongly correlated with a previously established, extensively tested polyclonal C-ELISA ( Blood 2008;112:4292–7) ( r  = 0.95, P  < 0.001). The area under the receiver operating characteristic curve for hepcidin as a predictor of ID, defined by 3 ferritin concentration thresholds, was >0.9. For predicting ID defined by ferritin <15 ng/mL, hepcidin <10 ng/mL yielded sensitivity of 93.1% and specificity of 85.5%, whereas the same hepcidin cutoff for ferritin <30 ng/mL yielded sensitivity of 67.6% and specificity of 91.7%. Conclusion: The clinical measurement of serum hepcidin concentrations was shown to be a potentially useful tool for diagnosing ID.